Prevalence of Undernutrition and Its Associated Factors among Children below Five Years of Age in Bure Town, West Gojjam Zone, Amhara National Regional State, Northwest Ethiopia - Desalegne Amare; Ayenew Negesse; Baye Tsegaye; Birtukan Assefa; Birehanu Ayenie (Advances in Public Health)
Background. Malnutrition is the major public health problem over the world. Developing countries are highly affected. Asian and Sub-Saharan African countries, including Ethiopia, contribute the highest of all. The main aim of this study was to assess the prevalence of undernutrition and its associated factors among children below five years of age. Methods. Community-based cross-sectional survey was conducted on 342 study participants. Simple random sampling technique was used to select sampling kebeles and study units. Weight and height were measured using calibrated instruments. The data were entered into EpiData version 3.1 software and calculated using SPSS version 20.0 statistical software and/or World Health Organization Anthro software with aid of Stat/Transfer. Results. Overall prevalence of undernutrition was 35.5%, of which 85 (24.9%), 38 (11.1%), and 49 (14.3%) were stunting, wasting, and underweight, respectively. Male children were more affected in both severe and moderate nutritional problems compared to female children. The finding showed that 27 (7.9%) had severe stunting, 15 (4.4%) had severe wasting, and 11 (3.2%) had severe underweight, respectively. Conclusion. Undernutrition was high in Bure town among children below five years of age. Male sex, maternal educational status, low household income, preterm babies, absence of antenatal follow-up, diarrhea, and respiratory infections within one-month duration were factors affecting undernutrition.